A Woman in the Far North: - Isabelle Gapp (Kunst og Kultur)
This essay draws attention to Anna Bobergʼs glacial landscapes, placing her in conversation with white, women polar explorers and Norwegian glacial art history during the nineteenth and early twentieth century. By challenging the narrative of the polar north as a male-gendered space, Bobergʼs en plein air glacial studies, alongside photographs of the artist in Arctic Norway, offer a novel and far northern perspective to an emergent ecocritical art history.